Relasi Kurikulum dan Pembelajaran serta Kontekstualisasinya dengan Nilai-Nilai Multikultural - Winarto Eka Wahyudi (Universitas Islam Lamongan, 2019)
This article discusses the relationship between curriculum and teaching and its contextualisation in learning with multicultural values. This study is very relevant considering that Indonesia is a nation that consists of diverse ethnic groups and is rich in cultural and religious differences. This anthropological inevitability requires an ability that is compatible with existing cultural realities. In this context, education plays an important role in giving birth to people who do not stutter from differences. To that end, designing a curriculum with multicultural values while translating it into the learning process is an effort to continue to be actualized. The relational model between curriculum and teaching that allows in internalizing multicultural values includes: the dualistic model, the interlocking model, the concentric model and the cycle model.